2017
DOI: 10.1021/acsmedchemlett.7b00138
|View full text |Cite
|
Sign up to set email alerts
|

Photoaffinity Labeling of the Human A2A Adenosine Receptor and Cross-link Position Analysis by Mass Spectrometry

Abstract: Photoaffinity labeling (PAL) is widely used for the identification of ligand-binding proteins and elucidation of ligand-binding sites. PAL has also been employed for the characterization of G protein-coupled receptors (GPCRs); however, a limited number of reports has successfully identified their cross-linked amino acids. This report is the first of its kind to determine the cross-link position of the human A adenosine receptor by PAL with the novel diazirine-based photoaffinity probe .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Nowadays, it is sometimes possible to identify the residue captured in the crosslinking reaction using tandem mass spectrometry (MS/MS). However, MS/MS on GPCRs is only possible when large amounts of isolated receptor are available, as it is for instance the case of rhodopsin [ 72 ] or receptors obtained by either yeast [ 73 , 74 , 75 ] or bacterial expression [ 58 ].…”
Section: The Contact Interfacementioning
confidence: 99%
“…Nowadays, it is sometimes possible to identify the residue captured in the crosslinking reaction using tandem mass spectrometry (MS/MS). However, MS/MS on GPCRs is only possible when large amounts of isolated receptor are available, as it is for instance the case of rhodopsin [ 72 ] or receptors obtained by either yeast [ 73 , 74 , 75 ] or bacterial expression [ 58 ].…”
Section: The Contact Interfacementioning
confidence: 99%
“…Muranaka et al started from the not-so-A 2A R-selective SCH58261 scaffold [ 144 ] and incorporated the trifluoromethyl diazirine group to yield photoaffinity ligand 9 (Fig. 5 , Table 4 ) [ 120 ]. When purified hA 2A R was photolabeled with this ligand and subjected to protease digestion, cross-link positions were identified with LC-MS/MS.…”
Section: Covalent Ligandsmentioning
confidence: 99%
“…[35] Using the structures of highly potent A 2A AR antagonists 13 and 14,Muranaka and co-workers developed probes 15 and 16 to study its binding site on A 2A AR (Figure 4). [26] After initial assays demonstrated am ore than 30-foldh igher affinity of 16 over 15,o nly probe 16 was used in photolabelinge xperiments. Using humanA 2A AR, they found that 16 had been selectively crosslinked to the amino acid residue Tyr271 in TM7.…”
Section: Human a 2a Adenosine Receptor Antagonist Binding-site Identimentioning
confidence: 99%